2012
DOI: 10.1177/0886260512459384
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Orientation Disparities in History of Intimate Partner Violence

Abstract: Few studies have examined history of intimate partner violence (IPV) among sexual minorities. We assessed prevalence and predictors of IPV using a probability sample of California residents ages 18 to 70. Lifetime and 1-year IPV prevalence was higher in sexual minorities compared with heterosexuals but this was significant only for bisexual women and gay men. IPV of bisexual women, but not gay men, occurred in a heterosexual relationship. We tested whether the higher prevalence of IPV in gay men and bisexual w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
98
2
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(111 citation statements)
references
References 20 publications
8
98
2
3
Order By: Relevance
“…While problems in a relationships no doubt lead to personal distress, there is also a strong argument that an individual’s emotional distress can lead to irritability and hostility, that when expressed towards one’s partner can provoke conflict and even IPV (Marshall, Jones, & Feinberg, 2011). Although our cross-sectional data do not permit us to determine directionality, our study replicates recent work by Goldberg and Meyer (2013) who found that psychological distress was associated with IPV victimization among LB women. Furthermore, our results lend support to the self-medication hypothesis (Khantzian, 1985) by demonstrating that among lesbian women emotional distress is associated with drinking to cope which in turn is associated with greater alcohol use and problem drinking and these are directly associated with more BPV.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…While problems in a relationships no doubt lead to personal distress, there is also a strong argument that an individual’s emotional distress can lead to irritability and hostility, that when expressed towards one’s partner can provoke conflict and even IPV (Marshall, Jones, & Feinberg, 2011). Although our cross-sectional data do not permit us to determine directionality, our study replicates recent work by Goldberg and Meyer (2013) who found that psychological distress was associated with IPV victimization among LB women. Furthermore, our results lend support to the self-medication hypothesis (Khantzian, 1985) by demonstrating that among lesbian women emotional distress is associated with drinking to cope which in turn is associated with greater alcohol use and problem drinking and these are directly associated with more BPV.…”
Section: Discussionsupporting
confidence: 80%
“…Furthermore, depressive symptoms specifically predicted subsequent bidirectional IPV among young adult heterosexual couples (Melander, Noel, & Tyler, 2010). To our knowledge no prospective study has found a link between emotional distress and IPV among lesbian women, although reports of past year psychological distress (i.e., feeling depressed, hopeless, restless) were cross-sectionally associated with past year IPV victimization in a sample that included heterosexual, lesbian, and bisexual women (Goldberg & Meyer, 2013). …”
Section: Emotional Distress and Ipv Among Lesbian Womenmentioning
confidence: 98%
“…Specifically, lesbian women who reported daily or weekly binge drinking were more likely to report physical and sexual relationship violence (Goldberg & Meyer, 2013). Also, in a sample of women with a history of IPV in the past five years, Eaton et al (2008) found a non-significant trend between hazardous alcohol use and same-sex IPV (defined as physical, sexual, and psychological aggression as well as property destruction and threatening to disclose sexual orientation).…”
Section: Mediators Of the Sexual Minority Stress - Ipv Associationmentioning
confidence: 99%
“…However, intimate partner violence (IPV) is not exclusive to opposite-sex relationships, and there is a growing body of research highlighting the prevalence of IPV in same-sex relationships [8][14]. Recent reviews suggest that the prevalence in same-sex couples, in particular male–male couples, is as high as or higher than it is for women in opposite-sex relationships [15][18]. The reported lifetime experience of IPV in gay male relationships lies between 15.4% and 51% [9],[11],[15],[18], depending on the population studied [11],[17], the definition of “partner” or “relationship” [11], and the type of measures used [19].…”
Section: Introductionmentioning
confidence: 99%